2002
DOI: 10.1161/01.cir.0000039104.56479.42
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Monotherapy With Eplerenone, a Novel Aldosterone Blocker, on Progression of Left Ventricular Dysfunction and Remodeling in Dogs With Heart Failure

Abstract: Background-In heart failure (HF), aldosterone has been implicated in the formation of reactive interstitial fibrosis, a maladaptation that contributes to left ventricular (LV) remodeling. Eplerenone is a novel selective aldosterone blocker. The present study examined the effects of long-term monotherapy with eplerenone on the progression of LV dysfunction and remodeling in dogs with chronic HF. Methods and Results-HF was produced in 14 dogs by intracoronary microembolizations that were discontinued when LV eje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
2
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(145 citation statements)
references
References 30 publications
8
129
2
6
Order By: Relevance
“…Aldosterone also increased and MR blockade reduced vascular inflammation and metalloproteinase-2 and -9 activation, suggesting that aldosterone may play a role in plaque rupture. 67 These effects are Figure 2. Mechanisms of genomic (longterm) and nongenomic (rapid) aldosterone (Aldo) effects.…”
Section: Integrative Molecular Physiology Of Vascular Effects Of Aldomentioning
confidence: 98%
“…Aldosterone also increased and MR blockade reduced vascular inflammation and metalloproteinase-2 and -9 activation, suggesting that aldosterone may play a role in plaque rupture. 67 These effects are Figure 2. Mechanisms of genomic (longterm) and nongenomic (rapid) aldosterone (Aldo) effects.…”
Section: Integrative Molecular Physiology Of Vascular Effects Of Aldomentioning
confidence: 98%
“…18 Reduced MIBG uptake into presynaptic sympathetic nerve terminals, as measured by a reduced MIBG heart-to-mediastinum ratio, reflects reduced beta AR density in heart failure patients. It also is strongly correlated with heart failure progression and cardiac death in heart failure patients with left ventricular dysfunction.…”
mentioning
confidence: 99%
“…It has been reported that aldosterone synthesis in local cardiac tissues and its effects are related with the process of left ventricular remodeling (26). Aldosterone blockers have been reported to suppress cardiac hypertrophy and cardiac fibrosis (27,28). Takeda et al reported that a high-salt intake accelerates the expression of the aldosterone synthase gene, CYP11B2 mRNA, in the cardiac tissues while also increasing cardiac aldosterone synthesis locally, which may affect cardiac hypertrophy independently of the RAAS in blood (29).…”
Section: Discussionmentioning
confidence: 99%